Modulation of Ion Channels in the Axon: Mechanisms and Function - Burke, Kenneth J.; Bender, Kevin J. (Frontiers in Cellular Neuroscience, 2019)
The axon is responsible for integrating synaptic signals, generating action potentials (APs), propagating those APs to downstream synapses and converting them into patterns of neurotransmitter vesicle release. This process is mediated by a rich assortment of voltage-gated ion channels and vesicle exocytosis machinery. Moreover, neuromodulators control the activity of these proteins through G-protein coupled receptor (GPCR) signaling cascades. Here, we review cellular mechanisms and signaling pathways involved in axonal ion channel neuromodulation and examine how changes to ion channel function affect AP initiation, AP propagation, and the release of neurotransmitter. We then examine how these mechanisms could modulate synaptic function by focusing on three key features of synaptic information transmission: synaptic strength, synaptic variability, and short-term plasticity. Viewing these cellular mechanisms of neuromodulation from a functional perspective may assist in extending these findings to theories of neural circuit function and its neuromodulation.